Intestinal Fibrosis in Inflammatory Bowel Disease and the Prospects of Mesenchymal Stem Cell Therapy - Wang, Yifei; Huang, Bin; Jin, Tao; Ocansey, Dickson Kofi Wiredu; Jiang, Jiajia; Mao, Fei (Frontiers in Immunology, 2022)
Intestinal fibrosis is an important complication of inflammatory bowel disease (IBD). In the course of the development of fibrosis, certain parts of the intestine become narrowed, significantly destroying the structure and function of the intestine and affecting the quality of life of patients. Chronic inflammation is an important initiating factor of fibrosis. Unfortunately, the existing anti-inflammatory drugs cannot effectively prevent and alleviate fibrosis, and there is no effective anti-fibrotic drug, which makes surgical treatment the mainstream treatment for intestinal fibrosis and stenosis. Mesenchymal stem cells (MSCs) are capable of tissue regeneration and repair through their self-differentiation, secretion of cytokines, and secretion of extracellular vesicles. MSCs have been shown to play an important therapeutic role in the fibrosis of many organs. However, the role of MSC in intestinal fibrosis largely remained unexplored. This review summarizes the mechanism of intestinal fibrosis, including the role of immune cells, TGF-β, and the gut microbiome and metabolites. Available treatment options for fibrosis, particularly, MSCs are also discussed.